KONTRIBUSI KOMPETENSI TERHADAP KINERJA PEGAWAI DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN TASIKMALAYA - Sahna Cahyadini; Astri Siti Fatimah; Ivan Dicksan (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
This research is motivated by the low performance of employees which is suspected to be influenced by employee competencies that are not fully in accordance with job demands. This study aims to determine the contribution of competency to employee performance at the Department of Transportation, Communication, and Informatics of Tasikmalaya Regency. The research method used is quantitative with an associative approach. The study population amounted to 43 employees using a stratified random sampling technique. Data were collected through observation, interviews, questionnaires, and literature studies. Data analysis used simple linear regression, t-test, and coefficient of determination with the help of SPSS version 25. The results of the study indicate that competency contributes positively and significantly to employee performance with a coefficient of determination of 38.5%, while 61.5% is influenced by other factors outside the study. Thus, competency which includes knowledge, skills, and attitudes plays an important role in improving employee performance. Keywords: Competence; Employee performance; Human Resources.